Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Matematika Bertipe Hots Pada Materi Himpunan - Kii, Ansila Ina; Making, Samuel Rex M.; Lede, Yulius Keremata (Varied Knowledge Journal, 2023)
This study aims to determine student errors clearly VII SMPK St. Paul Karuni in solving HOTS-type math problems on set material. This type of research is descriptive with a qualitative approarch. Data analysis techniques use steps consisting of 3 steps, namely: data reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be concluded that the types of errors that arise when students solve the set material story problem are 1) errors in understanding the problem, where students do not complete writing down what is known in the question and does not write down what is known and what is asked in the question. 2) transformation error, where students cannot change the problem from story form to mathematical form and do not complete the solution. 3) Process skill errors, where students are unable to perform calculations. 4) Errors in writing the final answer, where students write the final answer that does not match in the question.Factors in students that cause student errors are not having the ability to write down things that are known and asked in the problem, rushing to solve the problem, not having the ability to do the correct solution, and not understanding the calculations used.